Obstructive Urolithiasis in Small Ruminants - Kanika Tiwari; N. S. Jadon; Jyotsana Bhatt (The Indian Veterinary Journal, 2023)
A clinical study was conducted on 15 male calves and 6 male goats presented at TVCC, Pantnagar from August, 2021 to February, 2022 with history of anorexia, abdominal distention and urine retention. Examination revealed obstructive urolithiasis in calves. Animals were operated and Foley’s catheter was applied in urinary bladder for providing temporary pathway for urine evacuation. Animals were administered antibiotic, anti-inflammatory drug IM for 1 week and ammonium chloride PO for 1 month. After 12th day post-operative, sutures were removed. Foley’s catheter was removed after urine resumed through the normal route. All the animals recovered uneventfully.